Cyber Notary In The Indonesian Legal System: Its Urgency and Implementation - Gustianus Fernando; Gunawan Djajaputra (International Journal Labs, 2025)
Advances in information technology have driven transformation in various sectors, including the legal field, especially the notary profession. This article aims to analyze the urgency and challenges of the implementation of cyber notary in the Indonesian legal system. The method used is a juridical-normative approach with an analysis of relevant laws and regulations and a comparative study of cyber notary practices in other countries, such as the United States and Estonia. The results of the study show that cyber notaries offer various advantages, such as time and cost efficiency, increased access to legal services in remote areas, and adaptability in emergency conditions such as pandemics. However, its implementation in Indonesia faces significant obstacles, including regulatory limitations that still require physical presence in the making of deeds, weak technological infrastructure, and low digital literacy among notaries and the public. The discussion emphasized that without legal reform and strengthening of the cybersecurity system, the implementation of cyber notary will only be a concept without realization. It is necessary to revise the Law on the Notary Position and the establishment of special regulations that regulate online procedures, digital identity validation, and a valid and secure electronic document storage system. In conclusion, cyber notaries are an urgent need in the digital era. With the right legal, technological, and socialization support, this system can become an integral part of the modernization of notary services in Indonesia.